2019
DOI: 10.1093/jrr/rrz010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of radiotherapy in advanced external auditory canal cancer

Abstract: External auditory canal cancer (EACC) is a rare malignant tumor. In the present study, we retrospectively evaluated the treatment results in patients with advanced EACC who were treated using external-beam radiotherapy (EBRT) combined with chemotherapy or radical surgery. Overall, 21 patients with Stage III ( n = 8) or Stage IV ( n = 13) EACC who underwent initial treatment at our hospital between 2003 and 2016 were enrolled in this study. The 2-year overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…They concluded that definitive CRT, surgery, and adjuvant chemotherapy resulted in equivalent OS of the patients. In recent studies, they found that definitive CRT showed equivalent survival rates of patients with advanced EAC cancer compared to surgical treatment 6,7,9,13 . In fact, approximately two‐thirds of the patients with EAC cancer in our series underwent CRT, and their treatment outcomes were almost equal to those of the patients who underwent surgical treatment (Figure 2).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…They concluded that definitive CRT, surgery, and adjuvant chemotherapy resulted in equivalent OS of the patients. In recent studies, they found that definitive CRT showed equivalent survival rates of patients with advanced EAC cancer compared to surgical treatment 6,7,9,13 . In fact, approximately two‐thirds of the patients with EAC cancer in our series underwent CRT, and their treatment outcomes were almost equal to those of the patients who underwent surgical treatment (Figure 2).…”
Section: Discussionmentioning
confidence: 57%
“…In recent studies, they found that definitive CRT showed equivalent survival rates of patients with advanced EAC cancer compared to surgical treatment. 6,7,9,13 In fact, approximately two-thirds of the patients with EAC cancer in our series underwent CRT, and their treatment outcomes were almost equal to those of the patients who underwent surgical treatment (Figure 2). The 3-year overall survival rate of 55.0% of the patients with T4 EAC cancer was at least as much as that of the previous reports (Table 5).…”
Section: Discussionmentioning
confidence: 69%
“…Shiga et al showed that T4‐classified tumors were treated primary with chemoradiotherapy when the tumor involves the cochlear, jugular foramen, dura mater invasion, or brain invasion 30 . Results of other studies also presented beneficial effects of chemoradiotherapy on survival outcomes of EAC SCC, but all studies used different chemoradiation protocols and the sample sizes were too small for meaningful evaluation 31–38 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on treatment strategies for EAC cancer concluded that a combination treatment of surgery and postoperative radiation was the most curative for T2−3 disease [3,5,6,16,17]. However, adverse events from surgery are not uncommon [3,18].…”
Section: Discussionmentioning
confidence: 99%